A Family-Mediated Behavioral Home Literacy Program to Support Developmental Vulnerabilities: Habilitative Outcomes for Preschoolers Exhibiting Sluggish Cognitive Tempo (SCT)/Cognitive Disengagement Syndrome (CDS) - Avci, Alperen; Yalman Polatlar, Duygu (Routledge Journals, Taylor & Francis Ltd, 2026)
This study examined the effects of a family-mediated, naturalistic behavioral home literacy intervention on preschool children exhibiting Sluggish Cognitive Tempo (SCT)/Cognitive Disengagement Syndrome (CDS). Using a mixed design with three parent-child dyads, changes in the home literacy environment, parent-child interaction patterns, and children's early literacy, numeracy, and executive function-related performance were evaluated. Results indicated intervention-related behavioral improvements in parents' literacy-supportive behaviors and positive interaction patterns, alongside marked and sustained gains in children's task engagement, academic performance, and executive functioning. Overall, the findings highlight the potential of parent-mediated behavioral home literacy interventions as effective habilitative supports for preschool children with attentional and self-regulatory vulnerabilities.
Keywords: Home Literacy Environment; Sluggish Cognitive Tempo; Cognitive Disengagement Syndrome; Preschool Children